2018
DOI: 10.1002/ece3.4372
|View full text |Cite
|
Sign up to set email alerts
|

Food quality and quantity are more important in explaining foraging of an intermediate‐sized mammalian herbivore than predation risk or competition

Abstract: During times of high activity by predators and competitors, herbivores may be forced to forage in patches of low‐quality food. However, the relative importance in determining where and what herbivores forage still remains unclear, especially for small‐ and intermediate‐sized herbivores. Our objective was to test the relative importance of predator and competitor activity, and forage quality and quantity on the proportion of time spent in a vegetation type and the proportion of time spent foraging by the interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 65 publications
2
30
2
Order By: Relevance
“…Goszczyński and Wasilewski (1992) also suggested that foxes might be more successful in capturing hares in forests compared to open fields, suggesting that higher vegetation increases predation risk. Our findings are in contrast to Weterings et al (2018), who found that hares increasingly used areas of low forage quality (i.e., high vegetation) when predator activity increased. These differences might be caused by differences in the habitat structure, with our study conducted in a highly agricultural landscape compared to a coastal‐dune landscape in Weterings et al (2018), and emphasize that habitat differences can affect anti‐predator behavior, as shown in other species (Abu Baker & Brown, 2014; Cappa, Campos, Giannoni, & Andino, 2017), and should thus be taken into account.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Goszczyński and Wasilewski (1992) also suggested that foxes might be more successful in capturing hares in forests compared to open fields, suggesting that higher vegetation increases predation risk. Our findings are in contrast to Weterings et al (2018), who found that hares increasingly used areas of low forage quality (i.e., high vegetation) when predator activity increased. These differences might be caused by differences in the habitat structure, with our study conducted in a highly agricultural landscape compared to a coastal‐dune landscape in Weterings et al (2018), and emphasize that habitat differences can affect anti‐predator behavior, as shown in other species (Abu Baker & Brown, 2014; Cappa, Campos, Giannoni, & Andino, 2017), and should thus be taken into account.…”
Section: Discussioncontrasting
confidence: 99%
“…Camera traps recorded fewer hares with increasing vegetation height, which is in line with previous findings showing that active hares generally select for short vegetation (Mayer et al, 2018), because they are of better forage quality (Weterings et al, 2018). This might also explain why hare and roe deer numbers were correlated, that is, they have similar foraging patterns within agricultural areas.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This behavioral flexibility has also been observed in many other primate species, such as Colobus angolensis palliates (Dunham, 2017) and Cercopithecus albogularis labiatus (Nowak, Wimberger, Richards, Hill, & Roux, 2017; Wimberger, Nowak, & Hill, 2017). For these species, the risk of starvation and sensitivity to fruit availability may be more important than the risk of predation induced by human disturbance (McLennan, 2013; Nowak et al, 2017; Weterings, Moonen, Prins, Wieren, & Langevelde, 2018). This implies that the nonavoidance of human settlements by chimpanzees may be a consequence of their pursuit of agricultural foods.…”
Section: Discussionmentioning
confidence: 99%